Health-related goals and happiness — the associations among South African youth - Davids, Eugene Lee (Health Promotion & Physical Activity, 2024)
Introduction: Self-Determination Theory is a theory of motivation, health, well-being, and development. It is suggested that goals and aspirations become important in health and well-being. The health-related life goals and aspirations are often ambiguous in nature when examining happiness. The current study, therefore, aimed to examine health-related goals and subjective happiness among South African youth. Materials and methods: Using a cross-sectional design, the study included 1411 participants with a mean age of 21.81 years, who were largely female from eight of the nine provinces in South Africa. Data was collected via a secure, online platform using the Aspirations Index and the Subjective Happiness Scale. All data in the study were analysed using the Statistical Package for the Social Sciences for both descriptive and inferential statistics. Results: The results suggest that the health-related life goal and aspiration ‘to keep myself healthy and well’ was the only significant predictor of subjective happiness among the sample of South African youth. The model examined, explained 4.5% of the variance and the results suggest that the model was significant. The results suggest that the goal content and why goals and aspirations are aspired towards become important when examining health and happiness. Conclusions: Recommendations are provided for further research into the interaction between health, happiness, well-being, and psychological flexibility to inform research and practice.